Clinical and anamnestic predictors of stress urinary incontinence in women - Anna A. Mikhelson; Evgenia Vladimirovna V. Lugovykh; Maria V. Lazukina; Anatoly N. Varaksin; Ksenia D. Lukianova; Elizaveta M. Minyailo (IP Berlin A.V., 2022)
Aim.To study clinical and anamnestic predictors of stress urinary incontinence in postmenopausal women. Materials and methods.A retrospective cross-sectional study in which 89 women participated. Group 1 (main) included 57 women with stress urinary incontinence. Group2 (comparison group) included 32 women who do not suffer from SUI. Statistical processing was carried out using a package of applied programs, Excel, SPP Statistics 22.0. For indicators characterizing qualitative signs, the absolute value and the relative value in percent were indicated; the chi-square test was used to test statistical hypotheses. Statistical hypotheses about the absence of intergroup differences for quantitative traits with a normal distribution were tested using the Student's t test. The data obtained indicate that active sports (gymnastics, weightlifting, rowing, tennis), leading to an increase in intra-abdominal pressure, are one of the main reasons for the development of SUI. Results.A statistically significant higher BMI value was found in women with SUI than in women in the comparison group. According to the chi-square test and Spearman's coefficient, a tendency was revealed for an increase in the proportion of women with urinary incontinence with an increase in the number of births of more than two. Predictors of the development of SUI are previous births through the vaginal birth canal, their number is more than three, births weighing more than 4000 grams and complicated by obstetric injuries. When evaluating comorbidities, it was found that patients with SUI were statistically significantly more likely to suffer from diseases of the cardiovascular and respiratory systems, as well as from disorders of carbohydrate metabolism. Conclusion.The data obtained indicate the need and extreme importance of taking anamnesis, questioning women according to questionnaires, and clinical examination. The above measures should be paramount in the diagnostic search along with routine instrumental and laboratory diagnostics of stress incontinence.